Standardization of P-32 radioactive solution (Brazilian Journal of Radiation Sciences, 2017)
The standardization solution using three different methods is presented. The disintegration rate was determined by the CIEMAT/NIST and TDCR methods in liquid scintillator systems and self-absorption extrapolation method using 4π(PC)-β system. The results obtained for the activity of the 32P solution were compared and they agree within experimental uncertainties.